A comparison of weight gain between HIV exposed uninfected and HIV unexposed uninfected infants who received KMC at Chris Hani Baragwanath Academic Hospital - Mapatha, Leshata Abigail; Nakwa, Firdose Lambey; Mokhachane, Mantoa (Frontiers in Pediatrics, 2022)
Introduction: Kangaroo Mother Care (KMC) has been associated with improved growth in low birthweight infants and reduction in hypothermia, hypoglycaemia, apnoeas, sepsis, hospital stay and mortality. The growth of HIV-infected children is poorer than those who are HIV-uninfected. There is paucity of data on weight gain in the HIV-exposed uninfected (HEU) infants compared to HIV-unexposed uninfected (HUU) infants receiving KMC. Aim: This study compared the weight gain of HEU and infants HUU from admission to the KMC ward until 12 months corrected age (CA) follow-up visit. Methods: Retrospective record review of the neonates admitted in KMC at Chris Hani Baragwanath Hospital over a two-year period (2012-2013). The weight gain was assessed via weight velocity using the formula; weight/kg/day from admission to KMC to discharge, and g/ week at term, 3, 6 and 9- and 12-months (CA). The demographics were collected and analysed using Statistica. Results: Seventy-seven (129/166) percent of the mothers were HIV negative. HIV negative mothers were younger (25.9 vs 31.6 years; p=0.000) and had fewer pregnancies (p=0.02). There was no difference between the gestational age (30.3±2.53 vs 30.8±2.88 weeks; p=0.35) and birthweight (1345g±234 vs 1314g±209; p= 0.47) between HEU and HUU. There were no differences in the weight gain (23.83g±12.2 vs 23.22g±15.2; p=0.83) in KMC. There was no differences in weight gain at the different follow-up time points between the two groups. Conclusion: Both HEU and HUU groups of infants showed reasonable weight gain despite maternal HIV status Key concepts: Kangaroo Mother Care (KMC), Low birth weight (LBW), HIV, HIV Exposed Uninfected (HEU), HIV Unexposed Uninfected (HUU), weight gain